Forests from the grass: natural regeneration of woody vegetation in temperate marginal hill farmland under minimum interference management - Pedley, David; McWilliam, Wendy; Doscher, Crile (Restoration ecology, 2023)
Marginal hill farmland is a key target for the restoration of temperate indigenous forest, which can help mitigate climate change and biodiversity loss. Reliance on natural regeneration and minimum interference management (MIM) is a low‐cost restoration strategy for farmers, with the transition from pasture to woody scrub vegetation (whether indigenous or exotic) an important early successional phase. However, few studies have determined the key factors that influence the regeneration of woody vegetation on pastoral farmland, nor the rate at which regeneration occurs. Using a geospatial analysis of a New Zealand pastoral hill farm subject to variable grazing and MIM, this study found that only 3.8% of grassland experienced detectable regeneration of woody vegetation over 16 years. The key factor influencing natural regeneration was proximity to existing woody vegetation, with the probability of regeneration decreasing as distance increased. Cattle grazing had a significant negative impact, with regeneration more likely to occur in areas free from cattle. Sheep grazing exhibited no significant positive or negative relationship with regeneration. To support natural regeneration of woody vegetation, landowners should prioritize areas with a higher presence of existing woody vegetation and exclude cattle. To increase the rate of regeneration, landowners should consider active management regimes and supplemental restoration strategies, such as applied nucleation and the introduction of nurse species. Given the increased cost and complexity of such approaches, effective government incentive programmes may be needed to provide landowners with financial support and expertise.